Serum flavin mononucleotide but not riboflavin is inversely associated with the risk of colorectal cancer. Issue 23 (7th November 2022) - Xu, Lei; Wu, Qi-Xin; Li, Xue; Fang, Yu-Jing; Zhou, Ruo-Lin; Che, Meng-Meng; Ma, Ting; Zhang, Cai-Xia
Abstract : Serum FMN, instead of riboflavin, was inversely associated with colorectal cancer risk in the Chinese population, especially among individuals with lower serum PLP and higher serum folate levels. Abstract : Vitamin B2 is essential for DNA methylation, stability and repair, which may influence the development and pathogenesis of several cancers. However, data regarding the associations of circulating vitamin B2 with colorectal cancer risk are limited. The purpose of this study was to investigate the associations between serum vitamin B2 and colorectal cancer risk, particularly among participants with different serum levels of vitamin B6 or folate. A hospital-based case–control study, including 1009 colorectal cancer cases and 1182 controls matched by age and sex, was conducted in Guangdong Province, China. Vitamin B2 including riboflavin and flavin mononucleotide (FMN), the vitamin B6 indicator pyridoxal-5′-phosphate (PLP) and folate in serum samples were measured by ultra-high-performance liquid chromatography–tandem mass spectrometry. Vitamin B2 sum was calculated as the sum of riboflavin plus FMN. A significant inverse association was observed between serum FMN, but not serum riboflavin or vitamin B2 sum, and colorectal cancer risk. The adjusted odds ratio (OR) and 95% confidence interval (95% CI) of serum FMN, by comparing the highest with the lowest quartile, was 0.63 (0.46–0.85, P trend = 0.001). Stratified analysis by serum PLP and folate levels indicated that serum FMN was inversely associated with colorectal cancer risk among participants with lower serum PLP or higher folate levels. This study added supporting data to the limited evidence that vitamin B2 could play a preventive role in colorectal carcinogenesis among the Chinese population, primarily by FMN. Individuals with a lower PLP level or an adequate folate level could be more sensitive to the protective role of vitamin B2 .